2006
DOI: 10.1002/art.22110
|View full text |Cite
|
Sign up to set email alerts
|

Feeling good rather than feeling better matters more to patients

Abstract: Objective. To determine the most appropriate means to assess the response to treatment in terms of pain and functional impairment in a chronic rheumatic condition (knee osteoarthritis [OA]) and an acute rheumatic condition (rotator cuff syndrome [RCS]). Methods. Two prospective studies were conducted consisting of 1,019 outpatients with knee OA and 271 patients with acute RCS. The minimal clinically important improvement and the patient acceptable symptom state were determined for knee OA pain using a visual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
166
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 183 publications
(171 citation statements)
references
References 11 publications
3
166
1
1
Order By: Relevance
“…Previous studies have reported that the MCID and PASS measure different things (12,23). Our data suggest that PASS and ROC cut points represent an upper limit of what patients can be expected to gain after THR, while the MCID represents a lower limit.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Previous studies have reported that the MCID and PASS measure different things (12,23). Our data suggest that PASS and ROC cut points represent an upper limit of what patients can be expected to gain after THR, while the MCID represents a lower limit.…”
Section: Discussionmentioning
confidence: 51%
“…In defining these estimators more precisely, future studies should focus on the interrelationship of all these parameters. Finally, we must also note that application of the MCID and PASS parameters to clinical practice must be done cautiously (12,23,32). These reference values are for groups, not individual patients.…”
mentioning
confidence: 99%
“…In recent years, groups, such as Outcome Measures in Rheumatoid Arthritis Clinical Trials (OMERACT) have explored both MCID and defining LDAS [17,56]. Recently, this has evolved into the minimal clinically important improvement (MCII) and the PASS in the work of Tubach et al, , 2006Tubach et al, , 2009. These were not included in the current evaluation as our data collection overlapped with the publication, and we did not field the indicators needed for MCII and PASS.…”
Section: Strengths and Limitationsmentioning
confidence: 89%
“…This in effect validates the approach(es) as well as providing information on error and predictive values. a ''patient acceptable symptom state (PASS)'' [15,16] or similarly a ''low disease activity state (LDAS)'' [17]. Any final score better than this threshold level would be a positive or satisfactory outcome statedregardless of the change it took to get there.…”
Section: Final Statementioning
confidence: 99%
“…They are appreciative if we can help them feel better, but ideally they don't just want to feel better, they want to feel good. 7,14,16 If possible, they probably want to feel as funkadelicly good as James Brown seemed to feel onstage. Numerous patient-reported outcome (PRO) measures have been developed to gauge the effect of our treatments on the way patients feel.…”
mentioning
confidence: 99%